PENGARUH MODEL CONSEPT SENTENCE (CS) TERHADAP KETERAMPILAN MENULIS PUISI BEBAS - Sartika, Dewi; Mering, Aloysius; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe main objective of this study: 1) To know the difference between learning model models Concept sentence (CS) and the conventional model of the skill of writing free verse 2) To determine differences in learning outcomes of higher student learning outcomes poor students in menelis free verse 3) to determine the effect of the interaction between the learning model dann learning outcomes of the skill of writing free verse 4) to megetahui differences in learning outcomes high students Yag taught using models Concept sentence (CS) with the conventional model, 5) for megetahui differences in learning outcomes of low student dijar with Concept model of sentence (CS) and the conventional model. The method used in quantitative research is experimental method uses a form of factorial ANOVA two-lane design 2 x 2. The data collection technique is a measurement technique, unstructured interviews, direct observation, and documentation. Test research hypotheses using ANOVA two lanes and a further test Tukey posthoc type to see the difference in average group. from the results of the hypothesis test taken five conclusions for this study: 1) the learning outcomes Concept sentence (CS) is better than conventional models, 2) the result of high learning students is greater than the result of a low learning students from the second grade, 3) there is an interaction effect between teaching methods and learning outcomes of students' writing skills free verse 4) group learning outcomes high students with models of Concept sentence (CS) is better than group learning outcomes of high student with the conventional model, 5) those learning outcomes of low student with models Concept sentence ( CS) is higher than the low group students' learning outcomes with conventional models. Keywords: Concept Sentence (CS), Learning, Conventional, Skills, Poetry Free